“I don’t think service changed, I think people changed”: Palliative care delivery in Aotearoa/New Zealand after COVID-19 - Rosemary Frey; Tess Moeke-Maxwell; Jackie Robinson; Deborah Raphael; Lisa Williams; Erica Munro; Jenny Thurston; Merryn Gott (Palliative Care and Social Practice)
Background: As a result of COVID-19 restrictions, palliative care services in New Zealand and across the world needed to adapt rapidly and creatively to find new ways of working, revising, and establishing new policies and practices. This article reports the findings of phase I of an 18-month study examining changes in hospice care delivery in Aotearoa/New Zealand in the wake of COVID-19. Objective: This study aimed to explore the motivations underpinning adaptations and innovations in the delivery of palliative care in the wake of COVID-19. Design: Transdisciplinary Action Research and Partnership approaches were utilised. Method: A thematic analysis was conducted of open-ended telephone, video, and in-person questionnaire data collected from January to August 2024 from a diverse group of stakeholders. Our findings explored the motivations for health professional practice changes in the realms of competence, relationships, and autonomy. Findings: Changes in behaviour involved streamlining and adapting policies and services, using technology to facilitate communication, building collaborative connections, and activating health professionals, families, and Indigenous empowerment. Conclusion: Palliative care services needed to adapt rapidly and creatively to the threats posed by COVID-19. The threats posed were a motivator to shift thinking about palliative care delivery regarding services, relationships, and empowerment. This shift in thinking led to changes in ways of working, revising, and establishing new policies and practices. The driving force underpinning the changes and innovations is the desire to provide patient-centred care. Indeed, the findings build a case for patient-centred, sustainable, and effective innovation. From the perspective of health professionals, the findings may inform strategies to sustain new practices in delivering quality palliative care. Additionally, they may also provide insights into possible methods to grow individual and community capacity to face future pandemics.